KÖNIGSBERG BOOK SCIENCE SCHOOL (1900–1945) - WALTER, AXEL E. (Knygotyra, 2015)
This survey gives an introduction to the research of the history of old Königsberg libraries and books that had been published from 1900 to 1945. It also discuss topical problems of modern bibliology focussed on the research perspectives of bibliographical reconstruction of the formerly Königsberg collections.